Acute sport-related concussion suppresses heart rate variability beyond clinical recovery. Issue 11 (25th May 2017) - Wright, Alexander D; Smirl, Jonathan D.; Grewal, Harjas S.; Bryk, Kelsey; van Donkelaar, Paul
Abstract : Objective: To examine the effect of acute sport-related concussion on heart rate variability (HRV) in contact-sport athletes over 1 month post-injury. Design: Prospective Cohort. Setting: Laboratory. Participants: 136 male contact-sport athletes (19.1±1.4 years) were recruited and a subset of 14 athletes sustained concussions (19±1.4 years) and were included in the current analyses. Intervention: Participants completed baseline (T0) and post-injury testing at 72-hours (T1), 2-weeks (T2), and 1-month (T3). A three-lead electrocardiogram was recorded to assess HRV during 5-minutes of quiet stance and while actively squatting at 0.10 Hz (6 squats per minute). Recordings were analysed using Kubios software (Kuopio, Finland). Independent variables included condition (resting versus active) and time (4). Outcome measures: Time-Domain: square root of mean squared differences of successive R-R intervals (RMSSD), percentage of successive R-R intervals that differ by more than 50 milliseconds (pNN50). Non-linear: approximate entropy (ApEn). Main results: RM-ANOVA revealed a significant main effect of time for ApEn only (p=0.016). ApEn was reduced at T2 (−0.126, 95% CI: 0.029–0.222, p=0.015) and T3 (−0.068, 95% CI: 0.009–0.128, p=0.027) compared to T0. Median return-to-play duration was 14.5 days. Conclusions: Acute sport-related concussions induce a delayed reduction in heart rate variability that does not manifest until near-clinical recovery, and persists until at least 1-month post-injury. This is an important finding, indicating that concussions impair regulation of the autonomic nervous system for a duration persisting well beyond clinical recovery. Competing interests: None.